KONFLIK BATIN TOKOH UTAMA DALAM NOVEL SRI KUNING KARYA R. HARDJOWIROGO (Kajian Psikologi Sastra) - Ratri, Tanti Sekar; Sri Harti Widyastuti; Mulyana ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2024)
The purpose of this study is to 1) describe the main characters, Srikuning and Sudjana, in the novel Sri Kuning by R. Hardjowirogo; 2) explain the nature of inner conflict; 3) identify the causing factors; and 4) explain how the characters resolve their conflict. This research used a qualitative descriptive method with Sigmund Freud's literary psychology approach that relates to the id, ego, and superego. The data collection technique is carried out through a literature study by reading carefully over and over again. The results of this study are as follows: 1) Srikuning's character: coquettish, assertive, wise, etc.; Sudjana's character: skilled in fighting, careful, honest, etc. 2) The form of Srikuning's inner conflict: anger, sadness, inner conflict, etc., whereas Sudjana's: anger, sadness, heartlessness, etc. 3) Factors that cause Srikuning's inner conflict: being set up by Subagja and Bendara Juru, being defamed by Bendara Juru, etc., whereas Sudjana's are: Subagja interfering with his affairs with Srikuning, being emotionally provoked by Pak Thiwul, etc. 4) Direct aggression, diversion, and rationalisation are Srikuning's methods of resolving conflict, whereas Sudjana uses regression and rationalisation to handle it.